(untitled) (Scientific journal of the Fergana State University, 2023)
The scientific significance of the social purpose of education is revealed, that every person is a representative of the value, spiritual culture in society. Another distinctive feature of this process is that education has been studied in terms of socialization to ensure the spiritual growth of each generation. The issue of spiritual education, which is important for the development of society, is scientifically based